Re-work Program in Japan—Overview and Outcome of the Program - Ohki, Yoko; Igarashi, Yoshio; Yamauchi, Keita (Frontiers in Psychiatry, 2021)
Background: The objective of this study was to examine the effect of the Japanese re-work program (RP) to aid in recurrent sick leave prevention. Methods: A multicenter retrospective cohort research was conducted for workers who returned to work (RTW) after sick leave due to mood disorder. Work continuation for subjects who RTW after RP participation and treatment as usual (TAU) and subjects who received TAU only were compared. The Kaplan–Meier method and Cox proportional hazard models were utilized. Additionally, propensity score matching was conducted to control for possible confounds. Results: Log-rank test of overall cohort (n = 323) showed that work continuation of RP + TAU subjects was significantly better compared to that of TAU-only subjects (p = 0.001). Multivariate analysis found a hazard rate of recurrent sick leave for TAU-only subjects of 2.121 (p = 0.001, 95% CI: 1.360–3.309). Additionally, the propensity score-matched cohort (n = 100) had similar differences (p = 0.008), with a hazard ratio of recurrent sick leave of 2.871 (p = 0.009, 95% CI: 1.302–6.331) for TAU-only subjects. Limitations: Only workers who RTW after sick leave were targeted, and no examination was made considering cases who dropped out from RP or TAU. Moreover, the sample was a non-randomized controlled trial, with propensity score matching performed. However, there was an inability to retrieve and adjust for working environment background factors after RTW. Conclusions: Work continuation of subjects with RP was observed to be significantly better, suggesting that the RP was effective for recurrent sick leave prevention.